1978
DOI: 10.1093/schbul/4.4.522
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Schizophrenia*

Abstract: This article suggests that social network concepts and methods can provide a unifying framework for social research on schizophrenia. A selective review of the literature indicates that a social network perspective is not only consistent with a range of other research approaches and findings, but may help resolve some basic and persistent methodological and conceptual problems. A theoretical model is briefly described which attributes a critical role in the onset and recurrence of schizophrenia to social netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
20

Year Published

1982
1982
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(63 citation statements)
references
References 83 publications
0
43
0
20
Order By: Relevance
“…Studies have shown that people diagnosed with schizophrenia have more restricted and dense social networks primarily composed of kin and that the quality of these network relations is often unsatisfactory. Weak social networks increase the likelihood of social isolation and exacerbate psychological symptoms, a pattern well-documented among individuals with schizophrenia over the last 25 years (e.g., Beels, 1978Beels, , 1981Hammer et al, 1978). To date, no studies have examined the social network dimensions of clubhouse consumers, specifically those living with schizophrenia.…”
Section: Defining and Measuring Social Network Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that people diagnosed with schizophrenia have more restricted and dense social networks primarily composed of kin and that the quality of these network relations is often unsatisfactory. Weak social networks increase the likelihood of social isolation and exacerbate psychological symptoms, a pattern well-documented among individuals with schizophrenia over the last 25 years (e.g., Beels, 1978Beels, , 1981Hammer et al, 1978). To date, no studies have examined the social network dimensions of clubhouse consumers, specifically those living with schizophrenia.…”
Section: Defining and Measuring Social Network Supportmentioning
confidence: 99%
“…Studies have historically shown that social support networks among people with SMI are typically characterized as more dependent and less reciprocal than those in the general population (Cohan & Sokolovsky, 1978;Froland, Brodsky, Olson, & Steward, 1979;Hammer, Makiesky-Barrow, & Gutwirth 1978). People living with schizophrenia, for example, are more likely to rely on a small and dense network of family members to provide support and are less likely to engage in a mutually reliant relationship (Beels, 1978;Green, Hayes, Dickinson, Whittaker, & Gilheany, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cobb 1976, Tolsdorf 1976, Hammer 1981, Winefield 1987, Sörensen and Dalgard 1988, Mitchell 1989, Nelson et al 1992, Biegel and Tracy 1994, Sörensen 1994, Albert et al 1998, Corrigan et al 2004, Cox 2006, Haber et al 2007, Dalgard and Sörensen 2009). Much of the research has been focused on definitions of social support and social networks, in addition to the identification of essential, active network factors such as size, quality, availability, density, reciprocity and utilization, how networks function and to what degree they facilitate service utilization and support recovery.…”
Section: Introductionmentioning
confidence: 99%
“…El tamaño medio de las redes para el total de los entrevistados es de 3,75 y dista mucho del número de vínculos disponibles para la población general, que oscila, según diversos estudios e instrumentos de evaluación, entre 8 y 10 personas aproximadamente (Golding y Baezconde-Garbanati, 1990;Gottlieb, 1981;Guimón et al, 1985;Hammer et al, 1978;McFarlane et al, 1980). Sin embargo, el tamaño varía en las diferentes tipologías analizadas, de modo que podemos distinguir redes medianas, formadas por seis o siete personas; pequeñas, de unas cuatro personas, y tan escasas que no llegan a los dos contactos de promedio.…”
Section: Análisis De Resultados Descripción Y Análisis De Los Tipos Dunclassified